Metformin and Micronutrient Status in Type 2 Diabetes: Does Polypharmacy Involving Acid-Suppressing Medications Affect Vitamin B12 Levels? - Wakeman M (Dove Medical Press, 2020)
Michael Wakeman, David T Archer Faculty of Health and Wellbeing, Sciences Complex, University of Sunderland, Sunderland SR1, UKCorrespondence: Michael WakemanFaculty of Health and Wellbeing, Sciences Complex, University of Sunderland, Sunderland SR1 3SD, UKTel +44 191 5153381Email mikepwakeman@gmail.comAbstract: Metformin is the first-choice drug in uncomplicated type 2 diabetes (T2DM) and is effective in improving glycaemic control. It is the most widely prescribed oral antidiabetic medicine and has a good safety profile. However, there is an abundance of evidence that metformin use is associated with decreased Vitamin B12 status, though the clinical implications of this in terms of increased risk of diabetic peripheral neuropathy are debated. There is growing evidence that other B vitamins, vitamin D and magnesium may also be impacted by metformin use in addition to alterations to the composition of the microbiome, depending on the dose and duration of therapy. Patients using metformin for prolonged periods may, therefore, need initial screening with intermittent follow-up, particularly since vitamin B12 deficiency has similar symptoms to diabetic neuropathy which itself affects 40– 50% of patients with T2DM at some stage. Among patients with T2DM, 40% are reported to experience symptomatic gastroesophageal reflux disease (GORD), of whom 70% use oral antidiabetic medications. The most common medications used to treat GORD are proton pump inhibitors (PPIs) and antagonists of histamine selective H2 receptors (H2RAs), both of which independently affect vitamin B12 and magnesium status. Research indicates that co-prescribing metformin with either PPIs or H2RAs can have further deleterious effects on vitamin B12 status. Vitamin B12 deficiency related to metformin and polypharmacy is likely to contribute to the symptoms of diabetic neuropathy which may frequently be under-recognised. This review explores current knowledge surrounding these issues and suggests treatment strategies such as supplementation.Keywords: H2 antagonists, diabetes, neuropathy, folic acid, magnesium, microbiome